Physical education department students: year-to-year physical progress tests and analysis - Irkhina, I.V.; Voronkov, A.V.; Ospishchev, V.P.; Grebtsova, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the dynamics in the physical fitness of the Physical Education Department students. Methods and structure of the study. Subject to the study were the 4-year students (2017 through 2020) of Belgorod State National Research University (n=72, 36 young women and 30 young men). The researchers used analysis and summaries of the reference scientific literature, physical fitness tests and standard mathematical statistical data processing toolkit. The experiment was 4 years long. Physical fitness was ranked excellent, good, moderate and low according to the GTO gold, silver, bronze badge and lower standards, respectively. Results and conclusion. The studies showed the Physical Education Department students’ physical fitness level remaining virtually same throughout the academic period, moreover some progress was noted in some physical fitness components. Knowing that the practical Physical Education training hours in the curriculum tend to fall by the fourth year, we may assume that the main reason for the specific progress is the still high interest and commitment for Physical Education in the students.